Innovative Business Development. Statistical Control of Processes in Six Sigma - Denis A. Zhevnov (Мир новой экономики, 2018)
Introduction. The success and competitiveness of any enterprise are facilitated by the introduction of innovative approaches and continuous improvement of technological processes. In addition, it is not enough simply to modernize the equipment. A comprehensive approach to the optimization of technology, the organization of an effective management system and the building of a corporate culture is needed. Effective implementation of changes is often hampered by an aggressive external environment that can nullify any innovations and improvements. The Six Sigma methodology offers tools that timely identify the negative effects of external and internal factors and help to eliminate their negative impact. Methods. The study is based on statistical and econometric methods. The graphs of the control are used to estimate the deviation from the statistically stable state. Calculations were made using a software package for the processing of statistical data Minitab. Results. Six Sigma has tools for statistical control that allow determining the causes that divert the process from the state of equilibrium. To do this, it is necessary to monitor key indicators recorded on the control charts. The result of the use of control charts are signals indicating the appearance of negative factors. In this article, practical case studies show how statistical stability can be used to improve the stability and efficiency of processes by making timely and informed management decisions. Discussion. The concept of Six Sigma has been successfully used for many years by leading world companies. Possessing effective tools to reduce variability and improve quality, it is becoming more and more in demand in our country. The application of the Six Sigma approaches in process optimization in Russian enterprises helps to improve the competitiveness and quality of domestic products, which is especially relevant in the context of the import substitution policy.